Effects of Root Pruning on Non-Hydraulic Root-Sourced Signal, Drought Tolerance and Water Use Efficiency of Winter Wheat - Shou-chen MA; Feng-min LI; Shen-jiao YANG; Chun-xi LI; Bing-cheng XU; Xu-cheng ZHANG (Journal of Integrative Agriculture, 2013)
Two pot experiments were conducted to study the effects of root pruning at the stem elongation stage on non-hydraulic root-sourced signals (nHRS), drought tolerance and water use efficiency of winter wheat (Triticum aestivum). The root pruning significantly reduced the root weight of wheat, but had no effect on root/shoot ratio at the two tested stages. At booting stage, specific root respiration of root pruned plants was significantly higher than those with intact roots (1.06 and 0.94 mmol g−1 s−1, respectively). The soil water content (SWC) at which nHRS for root pruned plants appeared was higher and terminated lower than for intact root plants, the threshold range of nHRS was markedly greater for root pruned plants (61.1-44.6% field water capacity) than for intact root plants (57.9-46.1% field water capacity). At flowering stage, while there was no significant difference in specific root respiration. The SWCs at which nHRS appeared and terminated were both higher for root pruned plants than for intact root plants. The values of chlorophyll fluorescence parameters, i.e., the effective photosystem II quantum yield (ϕPS II), the maximum photochemical efficiency of PS II (Fv/Fm), coefficient of photochemical quenching (qP), and coefficient of non-photochemical quenching (NPQ), in root pruned plants were significantly higher than in intact root plants, 7 d after withholding of water. Root pruned plants had significantly higher water use efficiency (WUE) than intact root plants in well-watered and medium drought soil, but not in severe drought condition. In addition, root pruning had no significant effect on grain yield in well-watered and medium drought soil, but significantly decreased grain yield in severe drought condition. In conclusion, the current study showed that root pruning significantly altered nHRS sensitivity and improved WUE of winter wheat in well-watered and medium drought soil, but lowered drought tolerance of winter wheat in severe drought soil. This suggests a possible direction of drought-resistance breeding and potential agricultural measure to improve WUE of winter wheat under semiarid conditions.